The Autonomy of Maritime Spaces - Arrese, Daniela (International Law E-books Online, Collection 2026., 2025)
The law of the sea is dominated by a private property paradigm that portrays coastal states' maritime spaces as mere appurtenances of a state's land territory. This paradigm underlies a prominent interpretation of UNCLOS, which holds that maritime spaces are unstable and contingent upon the movements of the coast. This view, however, poses serious threats to the legal order of the oceans, especially in the face of climate change-induced sea-level rise. By contrast, this book advances that maritime spaces can be conceived as autonomous, that is, independent of the land's physical changes and as part of the coastal state's territory.